The source and diversion of pharmaceutical drugs for non-medical use: A systematic review and meta-analysis. (1st May 2018) - Hulme, Shann; Bright, David; Nielsen, Suzanne
Highlights: Pharmaceuticals for misuse are mainly sourced by end-users through social networks. Pharmaceutical drugs are often obtained legitimately from doctors and then misused. Illegitimate practices like doctor shopping are infrequently reported by end-users. Sourcing via dealers is particularly common among people who use drugs. Little is known about how pharmaceutical dealers obtain their drug supplies. Abstract: Background: The non-medical use (NMU) of pharmaceutical drugs is an increasing public health concern. This systematic review consolidates current knowledge about how pharmaceutical drugs are obtained for NMU and the processes and people involved in diversion. Methods: Peer-reviewed and grey literature databases were searched for empirical studies published between 1996 and 2017 that examined the source or diversion of pharmaceutical opioids, sedatives or stimulants for NMU in countries with reported misuse problems. Pooled prevalence meta-analyses using random effects models were used to estimate the prevalence of medical and non-medical sourcing reported by end-users, and gifting, selling and trading by various populations. Results: This review synthesizes the findings of 54 cross-sectional studies via meta-analyses, with a remaining 95 studies examined through narrative review. Pharmaceutical drugs are primarily sourced for NMU from friends and family (57%, 95% CI 53%–62%, I 2  = 98.5, n = 30) and despite perceptions of healthcare professionals to the contrary, illegitimate practices such as doctor shopping are uncommon (7%, 95% CI 6%–10%, I 2  = 97.4, n = 29). Those at risk of diversion include patients displaying aberrant medication behaviors, people with substance use issues and students in fraternity/sorority environments. Sourcing via dealers is also common (32%, 95% CI 23%–41%, I 2  = 99.8, n = 25) and particularly so among people who use illicit drugs (47%, 95% CI 35%–60%, I 2  = 99.1, n = 15). There is little to no organized criminal involvement in the pharmaceutical black market. Conclusion: Pharmaceutical drugs for NMU are primarily sourced by end-users through social networks. Future research should examine how dealers source pharmaceutical drugs.